2019
DOI: 10.3390/microorganisms8010014
|View full text |Cite
|
Sign up to set email alerts
|

PYHIN Proteins and HPV: Role in the Pathogenesis of Head and Neck Squamous Cell Carcinoma

Abstract: In the last decades, the human papillomavirus (HPV) emerged as an etiological cause of head and neck squamous cell carcinoma (HNSCC), especially in the oropharynx. The role of two intracellular DNA sensors, which belong to the PYHIN family (interferon-inducible protein 16 (IFI16) and absent in melanoma 2 protein (AIM2)), has been analyzed in relation to HPV infection and head and neck carcinogenesis. In particular, IFI16 and AIM2 expression depends on HPV infection in HNSCC. They represent viral restriction fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 89 publications
0
7
0
Order By: Relevance
“…These chemokine responses may also be detrimental to HPV persistence, as evidenced by a recent mouse papillomavirus study where MmuPV1 was observed to specifically downregulate stress keratin-induced expression of CXCR3 ligands including CXCL10 [ 108 ]. IFI16 is a DNA-binding inflammasome component and can restrict HPV replication by epigenetically silencing viral gene expression reducing vDNA copy number [ 109 , 110 ]. Several of the genes upregulated by dsDNA transfection are counteracted by papillomavirus gene products.…”
Section: Discussionmentioning
confidence: 99%
“…These chemokine responses may also be detrimental to HPV persistence, as evidenced by a recent mouse papillomavirus study where MmuPV1 was observed to specifically downregulate stress keratin-induced expression of CXCR3 ligands including CXCL10 [ 108 ]. IFI16 is a DNA-binding inflammasome component and can restrict HPV replication by epigenetically silencing viral gene expression reducing vDNA copy number [ 109 , 110 ]. Several of the genes upregulated by dsDNA transfection are counteracted by papillomavirus gene products.…”
Section: Discussionmentioning
confidence: 99%
“…Another difference between HPV - and HPV + HNSCCs lies in expression of the two PYHIN proteins IFI16 and AIM2, the former nuclear and the second cytoplasmic sensors of double strand (ds) DNA. More specifically, while IFI16 is generally upregulated in HPV + HNSCC, AIM2 gene expression levels are usually found unchanged in HPV + HNSCCs with respect to their HPV - counterparts, where this gene is already expressed at high levels (10% vs. 50% of cases, respectively) [ 12 , 13 ].…”
Section: Head and Neck Squamous Cell Carcinomamentioning
confidence: 99%
“…In addition, APOBEC3B (A3B) has been involved in HPV + HNSCC mutagenesis [ 11 ]. Intriguingly, diminished exposure to exogenous carcinogens tends to favor APOBEC-mediated mutations of HPV + HNSCC, whereas HPV - HNSCC mostly retains a carcinogen-associated mutational profile [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tobacco, and betel nut use and genetic susceptibility are currently recognized worldwide as major HNSCC risk factors [3]. Moreover, human papillomavirus (HPV)-speci c subgroup infection (HPV16, HPV18) and dynamic change of the oral microbiome are also considered HNSCC promoting factors [5][6][7]. However, HNSCC pathogenesis remains unclear.…”
Section: Introductionmentioning
confidence: 99%